Fulminant Lyme myocarditis without any other signs of Lyme disease in a 37-year-old male patient with microscopic polyangiitis—a case report. Issue 3 (9th February 2022) - Schroeter, Marco R; Klingel, Karin; Korsten, Peter; Hasenfuß, Gerd
Abstract: Background: Lyme disease is a tick-borne multisystem infection. The most common cardiac manifestation is an acute presentation of Lyme carditis, which often manifests as conduction disorder and rarely as myocarditis. Case summary: We report the case of a 37-year-old male with a history of microscopic polyangiitis receiving immunosuppressive therapy. He was admitted for severe dyspnoea secondary to acute heart failure. Echocardiography and cardiac magnetic resonance imaging indicated a severely reduced left ventricular ejection fraction (LVEF) with global hypokinesia. Coronary heart disease was excluded, and endomyocardial biopsies (EMB) were performed. The left ventricular EMB revealed a rare case of fulminant Lyme carditis with evidence of typical lymphocytic myocarditis. Borrelia afzelii -DNA was detected without any relevant atrioventricular blockage or systemic signs of Lyme disease. The patient had no clinically apparent tick-borne infection or self-reported history of a tick bite. Immunological testing revealed a positive ELISA and Immunoblot for anti-Borrelia immunoglobulin G antibodies. After specific intravenous antibiotic therapy and optimized medical therapy for heart failure, the LVEF recovered, and the patient could be discharged in an improved condition. Repeat EMB a few months later revealed a dramatic regression of the cardiac inflammation and absence of Borrelia DNA in the myocardium. Discussion: A severely reduced LVEF can be the primary manifestation of Lyme disease even without typical systemic findings and can have a favourable prognosis with antibiotic treatment. A thorough workup for Lyme carditis is required in patients with unexplained heart failure, particularly with EMB, especially in immunosuppressed patients.